Respuesta :

Answer:

3, -3, -1/2

Step-by-step explanation:

There is no need to distribute, just set each parenthesis to equal to zero.

p(x)= (x-3)(x+3)(2x+1)

         X-3=0                     x+3=0                      2X+1=0

           +3  +3                     -3  -3                           -1  -1

             X=3                        X=-3                          2x=-1

                                                                                x=-1/2

So your answers are 3, -3, -1/2